Pengaruh Streamer Attractiveness, Content Marketing, dan Hedonic Shopping Motive terhadap Impulsive Buying dengan Utilitarian Value sebagai Pemoderasi - Lunardi, Lidya; Alexander; Tambun, Sihar (LP3kM Buddhi Dharma University, 2025)
This study investigates the impact of streamer attractiveness (SA), content marketing (CM), hedonic shopping motive (HSM), and utilitarian value (UV) on impulsive buying (IB) in the context of Indonesian e-commerce live streaming. It also examines how UV moderates the relationships between these factors and IB. A quantitative approach was adopted, using purposive sampling of 209 respondents who had previously participated in live shopping broadcasts. Data analysis was performed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that SA, CM, HSM, and UV all have a significant positive effect on IB, with HSM identified as the most dominant factor influencing impulsivity. Furthermore, UV moderates the relationship between SA and IB, but does not significantly enhance the effect of CM or HSM on IB. These results suggest that emotional drivers such as enjoyment and attractiveness are key catalysts for impulsive purchasing behavior. However, functional product value still plays a strategic role in driving purchase decisions. The study emphasizes the need for a balanced approach in content strategy, combining both emotional appeal and functional information to maximize consumer engagement and conversion. Marketers are encouraged to integrate hedonic (emotional) and utilitarian (practical) elements in their offerings to foster impulsive buying behavior. Additionally, future research should explore longitudinal and qualitative methods to capture the evolving nature of impulsive buying behavior, as well as the deeper psychological mechanisms driving consumer decisions in live commerce environments. Such research will help further uncover the dynamics of consumer decision-making in online shopping and improve understanding of the broader implications for e-commerce strategies.